IGF-I increases the expression of fibronectin by Nox4-dependent Akt phosphorylation in renal tubular epithelial cells - New, David D. (American Physiological Society, 2012)
Extracellular matrix accumulation contributes to the progression of chronic kidney disease. Many growth factors including insulin-like growth factor-I (IGF-I) enhance matrix protein accumulation. Proximal tubular epithelial cells (PTCs) synthesize matrix proteins. NADPH oxidases are major sources of reactive oxygen species (ROS), important signaling molecules that mediate biological responses in a variety of cells and tissue. We investigated the mechanism by which IGF-I regulates fibronectin accumulation in PTCs and the role of a potential redox-dependent signaling pathway. IGF-I induces an increase in NADPH-dependent superoxide generation, enhances the release of hydrogen peroxide, and increases the expression of NADPH oxidase 4 (Nox4) in PTCs. IGF-I also stimulates phosphorylation of Akt, and inhibition of Akt or its upstream activator phosphatidylinositol 3-kinase attenuates IGF-I-induced fibronectin accumulation. Expression of dominant negative Akt also inhibits IGF-I-induced expression of fibronectin, indicating a role for this kinase in fibronectin accumulation. Expression of dominant negative adenovirus Nox4 inhibits IGF-I-induced NADPH oxidase activity, Akt phosphorylation, and fibronectin protein expression. Moreover, transfection of small interfering RNA targeting Nox4 decreases Nox4 protein expression and blocks IGF-I-induced Akt phosphorylation and the increase in fibronectin, placing Nox4 and ROS upstream of Akt signaling pathway. To confirm the role of Nox4, PTCs were infected with adenovirus construct expressing wild-type Nox4. Ad-Nox4, but not control Ad-green fluorescent protein, upregulated Nox4 expression and increased NADPH oxidase activity as well as fibronectin expression. Taken together, these results provide the first evidence for a role of Nox4 in IGF-I-induced Akt phosphorylation and fibronectin expression in tubular epithelial cells.